Women empowerment and its relationship with wealth index and COVID-19 prevention - Akhmadi Akhmadi; Eli Amaliyah (International Journal of Public Health Science (IJPHS), 2022)
The pandemic requires empowering rural Indonesian women for their personal and family well-being and increased economic output because of their high participation in self-employment. This study aimed to find a relationship between women's empowerment, wealth level, and preventive behaviors towards the coronavirus disease 2019 (COVID-19). The study employed a cross-sectional design and was conducted at two community health centers in Banten, Indonesia. Women over 18 years old, married with at least one kid, and willing to participate were eligible. Over half of the 200 women were under 30 (56%) and had a higher degree (56.5%). Around 67.5% were unemployed, and 60% earned less than the regional minimum wage. Women were sufficiently empowered in terms of economic, household, and social empowerment. Preventive behaviors toward COVID-19 were connected with educational level, wealth index, women empowerment score, and knowledge, with an adjusted R square of 31%. Women who are empowered have a higher wealth index and COVID-19 prevention activities. It is argued that initiatives aimed at increasing women's empowerment would positively impact improving public health.